Astragalus Polysaccharides/PVA Nanofiber Membranes Containing Astragaloside IV-Loaded Liposomes and Their Potential Use for Wound Healing. (11th May 2022) - Yue, Yuan; Liu, Xinjun; Pang, Lan; Liu, Yue; Lin, Yuzhu; Xiang, Ting; Li, Jie; Liao, Shiqin; Jiang, Yunlan
Abstract : Delayed wound healing is a common and serious complication in diabetic patients, especially the slow healing of foot ulcers, which seriously affects the quality of life of patients and is also the most important risk factor for lower limb amputation. The multifunctional novel dressing prepared by loading the polymer nanofibers with anti-inflammatory and prohealing plant extracts can promote the wound repair of these ulcers by electrospinning technology. Liposomes are nanoparticles prepared from phospholipids and have been widely used as drug delivery systems. Liposomes can be combined with electrospun nanofibrous webs to facilitate local and sustained delivery of loaded bioactive substances. In this study, liposomes were prepared with astragaloside IV (AS) by employing a modified ethanol injection method and conducting the physical and chemical characterization (e.g., the particle size, polydispersity index, zeta potential, and entrapment efficiency). Astragalus polysaccharides were extracted from Astragalus membranaceus . Subsequently, we prepared the electrospun polyvinyl alcohol (PVA)/astragalus polysaccharide (APS)/astragaloside IV (AS) nanofibers. The morphology of the produced ASL/APS/PVA, APS/PVA, and PVA nanofibers were analyzed by scanning electron microscopy (SEM), and it turns out that the addition of astragalus extract made the fiber diameter smaller and the fibers arranged neatly with no dripping. An induced diabetic rat model was built, and a diabetic ulcer model was built by total cortical resection to assess the prorepair ability of the prepared nanofibers. According to in vivo animal experiments, the nanofibrous membrane loaded with APS and ASL was reported to inhibit the occurrence of wound inflammation, enhance the deposition of collagen fibers (P < 0.05 ) and the repair of regenerated epithelium (P < 0.05 ), and effectively strengthen the wound healing of diabetic rats (P < 0.05 ). In brief, PVA-loaded APS/ASL nanofibrous membranes refer to a prominent wound healing dressing material, which can effectively facilitate the healing of diabetic wounds, and they are demonstrated to be highly promising for application in diabetic wound dressings and tissue engineering.